Suicidio e autolesionismo in adolescenza Una proposta applicativa di multilevel governance transculturale - Stornello , Claudio; Pojani , Tiziana (Antropologia Pubblica, 2024)
Talking about suicide and self-harming among teenagers is not easy but it is necessary to do it, taking in account that pandemic from SARS-CoV-2 has exacerbated the two problems. The World Health Organisation (WHO) has published several documents on this topic, containing data and best practices to prevent and to treat cases, nevertheless not all countries have included laws or other initiatives to prevent those acts. The WHO recommend forming multi-sectoral teams to analyze data and facts and to find new solutions. Cultural differences and different expertise are important for these teams to think outside the box and to start the process of innovation with effective and smart proposals. Starting from these assumptions and considering the current regional rules of Friuli Venezia Giulia autonomous region (taken as case study) and pre-existing agreements, an innovative memorandum of understanding is proposed and described for that territory. In this process, the role of public anthropology can be relevant, helping to provide a broader point of view to the institutions and stakeholders involved. The document provides a new public body for suicide and self-harming prevention and a new way to manage cases together with families and schools, considering migrant minors not accompanied and their difficulties as well. In addition, it provides to make a network of public and private institutions to make them to work together and to share data, process, and forms.